Pengaruh Profitabilitas terhadap Audit Delay pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2024 - Kunta Ramadhan Ridwan Putra; Marcello Armando; Zaenal Abidin; Fikri Rizki Utama (Indo Publishing, 2026)
This study aims to determine the effect of profitability on audit delay in manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Profitability is measured using Return on Assets (ROA), while audit delay is measured based on the time difference between the financial statement date and the independent auditor’s report date. This study uses a quantitative approach with a sample of 5 manufacturing companies and 20 observational data. Data analysis techniques used include simple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that profitability has a negative and significant effect on audit delay with a significance value of 0.000 < 0.05. The regression equation obtained is Y=95.20-187.30X, indicating that the higher the company’s profitability, the lower the audit delay. The coefficient of determination value of 0.518 indicates that profitability explains 51.8% of audit delay, while the remaining 48.2% is influenced by other variables outside this study.